2020
DOI: 10.1039/d0cb00135j
|View full text |Cite
|
Sign up to set email alerts
|

Combining bacteriophage engineering and linear dichroism spectroscopy to produce a DNA hybridisation assay

Abstract: A novel DNA sensing method based on LD spectroscopy and using bionanoparticle scaffolds is described, as demonstrated by the rapid detection of DNA strands associated with bacterial and viral pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 26 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…We demonstrate that LD can provide unique insights into the structure and assembly process for the extended foldamer structures which can be used to optimize future foldamer designs. This data lays the foundations for the use of the foldamers in bioassays developed using LD as the detector …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…We demonstrate that LD can provide unique insights into the structure and assembly process for the extended foldamer structures which can be used to optimize future foldamer designs. This data lays the foundations for the use of the foldamers in bioassays developed using LD as the detector …”
Section: Introductionmentioning
confidence: 89%
“…This data lays the foundations for the use of the foldamers in bioassays developed using LD as the detector. 46…”
Section: ■ Introductionmentioning
confidence: 99%
“…( Michel et al, 2020 ; Trotter et al, 2020 ; Sun et al, 2019 ; Chen et al, 2019 ). This system has been previously developed for detection using antibodies ( Pacheco-Gómez et al, 2012 ) and DNA ( Ali et al, 2020 ) and offers high levels of sensitivity alongside speed and simplicity. Here we extend our work on this signal read-out methodology to encompass DNA aptamer-based detection.…”
Section: Introductionmentioning
confidence: 99%
“…We accordingly demonstrated that this novel LD sensing methodology could be used to detect pathogenic E. coli using antibodies ( Pacheco-Gómez et al, 2012 ) as well as DNA from pathogens. ( Ali et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation